Study of Methanolic Leaves Extract of Curcuma longa as an Anti-solar - Gajanan, Gharge Varsha; Milind, Gore Meghana; Adhikrao, Yadav (Current Research in Pharmaceutical Sciences, 2017)
The present study aimed at the phytochemical examination and anti-solar activity of Curcuma longa(leaf) methonolic extract has more flavonoid content based on this chemical substance photo protective activity was evaluated using UV visible spectrophotometry, where the method is diffused transmittance and the range of UV-visible about 200-400nm. The pulverized dried Curcuma longa leaves were extracted with Methanol using soxhlet apparatus. Methanol extract were filtered and evaporated to dryness. The photo protective activity was evaluated by using UV visible spectrophotometry, where the method it is diffused transmittance and the range of UV-visible about 200-400nm for absorption. The UV scanning absorption spectra of the extract showed very strong absorption 0.273 at 397 nm. The extract has an ability to absorb in the entire UV range.